A New Business Paradigm For The Electronic Commerce Of The Manufacturing Sector In Malaysia - Chia, Lee Joo (2001)
This paper will study on the new business paradigm , outsourcing of IT services, for the e-commerce of the Malaysian manufacturing sector on the awareness and impact of it.